Helicobacter pylori antibacterial resistance patterns in Latvia: results from the Gistar pilot study - D. Rudzīte; R. Vangravs; I. Daugule; Ģ. Šķenders; I. Poļaka; A. Vanags; J. Atstupens; I. Tolmanis; P. Pūpola; Y. Tarasenko; J. Park (Microbiota in Health and Disease)
Objective: The choice of the Helicobacter pylori (H. pylori) eradication regimen should depend on the antibiotic resistance of this major gastric pathogen. In Latvia, resistance patterns of H. pylori strains have not been described in the general population. The aim of the study is to evaluate the primary susceptibility of H. pylori to antibiotics used in recommended eradication regimens for the middle-aged population in Latvia.